2008
DOI: 10.2169/internalmedicine.47.1013
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Chitotriosidase Activity following Restoration of Euthyroidism in Patients with Subclinical Hypothyroidism

Abstract: Objective Whether to treat subclinical hypothyroidism (SH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Of the 36 articles initially selected, 12 studies were finally identified that met the inclusion criteria (▶Fig. 1) [10][11][12][13][14][15][16][17][18][19][20][21]. The characteristics of the subjects in both the SCH and euthyroid groups are summarized with the results in ▶table 1.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 36 articles initially selected, 12 studies were finally identified that met the inclusion criteria (▶Fig. 1) [10][11][12][13][14][15][16][17][18][19][20][21]. The characteristics of the subjects in both the SCH and euthyroid groups are summarized with the results in ▶table 1.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Hyperhomocysteinemia is proposed as a risk factor for CVD in those with overt hypothyroidism; yet, as SCH and overt hypothyroidism have a similar etiology, the tHcy level may also be valuable in patients with SCH. However, it is controversial whether SCH is associated with hyperhomocysteinemia; a few studies have shown that the tHcy level is elevated in those with SCH [10][11][12][13], while others have conflicting findings [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%